Healthy Eating: Calcium - Linda B. Bobroff (EDIS)
Calcium is the major mineral found in your bones and teeth. Many older adults don’t get enough calcium from the foods they eat. This can lead to bone loss and the bone disease osteoporosis. Osteoporosis puts people at high risk for bone fractures. This 1-page, large print fact sheets were written by Linda B. Bobroff and published by the UF Department of Family Youth and Community Sciences, June 2013.